Simon and the better bone - Tabor, Corey R. (Balzer + Bray, an imprint of HarperCollins Publishers, 2023)
One day, down by the pond, Simon meets another dog just like him. And that dog has a bone just like his, only better! How will Simon ever get him to trade, when the other pup knows all the same tricks? Using the same innovative format as his Caldecott Honor winner, Mel Fell, Corey R. Tabor reimagines Aesop's "The Dog and His Reflection" in a clever, charming tale of empathy and generosity.